Cutaneous IgG4-related disease treated with dupilumab - Mafalda Pestana; Alexandre João; Susana Palma-Carlos; Paula Leiria-Pinto; Ana L. João (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
We present a 59-year-old male with a prolonged history of severe, treatment-resistant pruritic dermatosis and associated systemic symptoms, including fatigue and diarrhea. Dermatologic examination revealed widespread erythematous-brownish papules and nodules, prompting a skin biopsy that showed dense infiltration by immunoglobulin G4 (IgG4)-positive plasma cells, leading to a diagnosis of IgG4-related disease (IgG4-RD). The patient was treated with dupilumab, resulting in complete skin lesion resolution and significant improvement in quality of life. IgG4-RD, a rare inflammatory disease with potential multiorgan involvement, frequently challenges diagnosis due to diverse clinical presentations. This case highlights dupilumab effectiveness as a novel therapy for IgG4-RD with cutaneous involvement, offering a promising alternative for patients who do not respond well to corticosteroids.